Traditional and hybrid solar photovoltaic array configurations for partial shading conditions: perspectives and challenges - Dharani Kumar Narne; T. A. Ramesh Kumar; RamaKoteswara Rao Alla (Bulletin of Electrical Engineering and Informatics, 2023)
he role of photovoltaic (PV) array in converting solar energy to electrical energy is very much important to get maximum power. Current challenge in solar PV systems is to make them energy efficient. Partial shading conditions (PSCs) is one of the main causes for performance degradation of PV array. It not only effects the shaded region but also effect the overall output of the PV array. Proper selection of configuration is essential to overcome such type of challenges. There exist various types of traditional configurations such as series (S), parallel (P), series parallel (SP), total-cross-tied (TCT), bridge-link (BL), and honeycomb (HC). Hybrid configurations also available such as series-parallel-total-cross-tied (SPTCT), bridge-link-total-cross-tied (BL-TCT), honey-comb- total cross-tied (HC-TCT), and bridge-link-honey-comb (BL-HC). This paper presents an overview on various types of configurations available with their merits and demerits under various partial shading situations. This paper also insights recent advancements in PV array configurations with their future trends to benefit the researchers working in this domain.